2020
DOI: 10.3390/ijerph17103477
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Histomorphometrical Evaluation of a New Implant Macrogeometry. A Sheep Study

Abstract: Decompression or healing chambers between the threads have been proposed to improve and accelerate the osseointegration process of dental implants. The aim of the present work was to test, in an in vivo sheep study, if healing chambers between the threads could produce a better osseointegration process. Thirty titanium implants (15 conventional design (control) and 15 implants with healing chambers (test)) were inserted in a random fashion in the tibia of 3 sheep. The animals were euthanized after 30 days of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 32 publications
(64 reference statements)
4
29
1
Order By: Relevance
“…The implant site osteotomy represents a key surgical phase to obtain primary stability during the screw positioning in clinical practice [1][2][3]. In the literature, the primary stability has been demonstrated as a necessary condition to obtain the osseointegration of the dental implant, in order to support the masticatory loading [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The implant site osteotomy represents a key surgical phase to obtain primary stability during the screw positioning in clinical practice [1][2][3]. In the literature, the primary stability has been demonstrated as a necessary condition to obtain the osseointegration of the dental implant, in order to support the masticatory loading [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…12 15 Comuzzi et al reported that, in standardized condition on low-density polyurethane study, the macro-geometry induced the main effect on the primary stability, while the osseodensification drilling procedure produced the more visible effect on stability in presence of a residual cortical bone. 16 Moreover, Gehrke et al reported the key role of the implant macro-geometry on a sheep study, while the self-tapping and round apex macro-geometry is able to influence significantly the percentage of new bone formation and the deposition of highly vascularized osteogenic matrix within the marrow spaces, 17 where the number and thickness of bone trabeculae increase with the loading of the dental implants. 18 In vivo, no radiographical and hystological evidence in crestal bone resorption were present were evident between the osseodensification procedure, 19 21 the drilling technique 22 and ultrasonic device approach.…”
Section: Introductionmentioning
confidence: 99%
“…The solid rigid polyurethane bone block has been proposed as a valuable material for orthopedics and maxillofacial medical devices [5,11,33]. The material is available in different densities and microstructures able to simulate the mechanical and physical properties of human bone and its cortical and cancellous components [34].…”
Section: Introductionmentioning
confidence: 99%